Metabolic Engineering and Synthetic Biology: Synergies, Future, and Challenges - García-Granados, Raúl; Lerma-Escalera, Jordy Alexis; Morones-Ramírez, José R. (Frontiers in Bioengineering and Biotechnology, 2019)
The "-omics" era has brought a new set of tools and methods that have created a significant impact on the development of Metabolic Engineering and Synthetic Biology. These areas, rather than working separately, depend on each other to prosper and achieve their individual goals. Synthetic Biology aims to design libraries of genetic components (promoters, RBS, coding sequences, terminators, transcriptional factors and their binding sequences, and more), the assembly of devices, genetic circuits and even metabolic pathways; in addition to obtaining quantitative information for the creation of models that can predict the behavior of biological systems (Cameron, D., et al., 2014). Metabolic engineering seeks for the optimization of cellular processes, endemic to a specific organism, to produce a compound of interest from a substrate, preferably cheap and simple. It uses different databases, libraries of components and conditions to generate the maximum production rate of a desired chemical compound and avoiding inhibitors and conditions that affect the growth rate and other vital functions in the specific organism; to achieve these goals; manipulating metabolic fluxes represents an important alternative (Stephanopoulos, G., 2012).